Psychological effects of COVID-19 outbreak in hospital workers during the Italian third phase (Working Paper of Public Health, 2021)
Objectives: The aim of the study was to explore the psychological impact of COVID-19 outbreak, during the so-called phase three of the infection in Italy, in healthcare workers and other professionals working in the Public Hospital “SS Antonio e Biagio e Cesare Arrigo” in the Piedmont Region.Methods: A monocentric prospective observational study was conducted on 113 hospital workers by completing an online survey. Data were collected from 29th June to 20th July 2020. The survey assessed self-reported socio-demographic, clinical, work and COVID-19 related information and risk perception. Moreover, it included an online version of validated questionnaires in the Italian language: Impact of Event Scale-Revised (IES-R), Depression, Anxiety and Stress Scale (DASS-21), Insomnia Severity Index (ISI), Coping Orientation to the Problems Experienced: COPE-NVI-25, and the Professional Quality of Life scale (ProQOl-5).Results: The exploratory analysis revealed that hospital workers showed a high percentage of post-traumatic stress symptoms in the months following the beginning of the pandemic. In general, having higher levels of education seems to be associated with less anxiety, stress, depression insomnia e post-traumatic stress symptoms. Those symptoms were reported among those who had higher risk perception, previous psychological problems, or suffered from a chronic disease. Workers with more than 10 years experience and low risk perception reported less insomnia symptoms.Conclusions: The assessment of psychological effects of COVID-19 outbreak might help to create good practices that could be used and improved to implement focused interventions on workers’ well-being, especially during COVID-19 and post COVID-19 periods.